2021
DOI: 10.1093/conphys/coab071
|View full text |Cite
|
Sign up to set email alerts
|

Water deprivation compromises maternal physiology and reproductive success in a cold and wet adapted snake Vipera berus

Abstract: Droughts are becoming more intense and frequent with climate change. These extreme weather events can lead to mass mortality and reproduction failure, and therefore cause population declines. Understanding how the reproductive physiology of organisms is affected by water shortages will help clarify whether females can adjust their reproductive strategy to dry conditions or may fail to reproduce and survive. In this study, we investigated the consequences of a short period of water deprivation (2 weeks) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 75 publications
(138 reference statements)
0
21
0
Order By: Relevance
“…Second, dehydration should induce compensatory physiological responses to mitigate water constraints. We predict, in particular, patterns of structural muscle catabolism to release bound water (Brusch et al, 2018) and a greater thirst reaction (Dezetter et al, 2021;Dupoué et al, 2014). Third, behavioural selection of wet microclimates should mitigate these effects by reducing evaporative water loss, especially when the simulated air is drier.…”
Section: Introductionmentioning
confidence: 95%
“…Second, dehydration should induce compensatory physiological responses to mitigate water constraints. We predict, in particular, patterns of structural muscle catabolism to release bound water (Brusch et al, 2018) and a greater thirst reaction (Dezetter et al, 2021;Dupoué et al, 2014). Third, behavioural selection of wet microclimates should mitigate these effects by reducing evaporative water loss, especially when the simulated air is drier.…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, within temperature treatments, females in wet or dry conditions gained similar relative mass per day, suggesting that females in wet conditions either drank less or females in dry conditions were able to reduce evaporative water loss. Temperatures were imposed by climatic chambers to eliminate the possibility of behavioral thermoregulation, but differences in transcutaneous or ocular water loss rates may have occurred due to changes in behavioral hydroregulation or plasticity of the skin barrier to transepidermal water loss (Dupoué et al 2015, Refsnider et al 2019, Dezetter et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, all females experienced muscle loss during the experiment and losses were highest in females in dry conditions, especially if they had limited access to preferred temperatures during the daytime. Muscle wasting during pregnancy is common in reptiles (Lourdais et al 2004, 2013, Lorioux et al 2016) and skeletal muscle has been shown to be an important substrate for the reallocation of hydric resources when demands are high and intake is limited (Brusch et al 2019, 2020, Dezetter et al 2021). Because proteins are a much lower energetic source compared to lipids and their oxidation provides five times more water (Jenni and Jenni‐Eiermann 1998), increased muscle catabolism likely supported the hydric costs of reproduction in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adder has several life‐history traits (limited movement, low frequency of reproduction, high costs of reproduction) that make it vulnerable to perturbation. The species is also particularly sensitive to microclimatic conditions and vulnerable to water loss (Guillon et al ., 2014; Dezetter et al ., 2021). There are important declines of adders elsewhere, notably in small isolated populations (Gardner et al ., 2019; Graitson, Barbraud, & Bonnet, 2019).…”
Section: Discussionmentioning
confidence: 99%